Decreasing distance from tumor to the language network causes language deficit. Issue 2 (28th September 2022) - Fang, Shengyu; Weng, Shimeng; Li, Lianwang; Guo, Yuhao; Zhang, Zhong; Fan, Xing; Jiang, Tao; Wang, Yinyan
Abstract: Preoperative language deficits are associated with alterations in the language networks of patients with gliomas. This study investigated how gliomas affect language performance by altering the language network. Ninety patients with lower‐grade gliomas were included, and their preoperative language performance was evaluated using the Western Aphasia Battery. We also calculated the topological properties based on resting state functional magnetic resonance imaging. All patients were classified according to aphasia quotient (AQ) into the aphasia (AQ < 93.8), mild anomia (AQ > 93.8 and naming section <9.8), and normal groups (AQ > 93.8). The shortest distance from the tumor to the language network (SDTN) was evaluated to identify the effect on language performance induced by the tumor. One‐way analysis of variance and post hoc analysis with Sidak correction were used to analyze the differences in topological properties among the three groups. Causal mediation analysis was used to identify indirectly affected mediators. Compared with the mild anomia group, longer shortest path length ( p  = .0016), lower vulnerability ( p  = .0331), and weaker nodal efficiencies of three nodes (right caudal Brodmann area [BA] 45, right caudal BA 22, and left BA 41/42, all p  < .05) were observed in the aphasia group. The SDTN mediated nodal degree centrality and nodal vulnerability (left rostroventral BA 39), which negatively affected the AQs. Conventional language eloquent and mirrored areas participated in the language network alterations induced by gliomas. The SDTN was a mediator that affected the preoperative language status in patients with gliomas. Abstract : Language dysfunction is a common neurological deficit in patients with gliomas, especially when the gliomas invade close to the eloquent area. This study investigated how gliomas affect language performance using graph theory. We found that the shortest distance between the tumor and language network strongly affected the language performance of patients with gliomas, and the aphasia and mild anomia groups had differently altered nodes to compensate for the damaged language function.